Application of low-cost materials coated with silver nanoparticle as water filter in Escherichia coli removal - Praveena, Sarva Mangala; Aris, Ahmad Zaharin (Springer, 2015)
The incorporation of silver nanoparticles into a range of low-cost materials as an antibacterial water filter treatment is a relatively new solution to drinking-water problems. This review discusses the use of potential low-cost materials (ceramic, polymeric, polyurethane, agricultural waste and fibre) by incorporating silver nanoparticles as an antibacterial water filter to remove Escherichia coli (E. coli). These low-cost materials have shown potential efficiency in the removal of E. coli, and the silver concentration in the effluent is below the permissible limits. Future perspectives and current knowledge gaps concerning low-cost materials incorporated with silver nanoparticles were also identified. The future perspectives (strengths and opportunities) of these low-cost materials include cost effectiveness, easy availability and consumption of minimal electricity. On the other hand, the knowledge gaps (threats and weaknesses) of these low-cost materials include the depletion of silver from the surface and the surface-coating technique. The potential risks to human health due to silver nanoparticles are still unclear and need more sensitive detection equipment and methods. Nevertheless, this review helps us determine the potential of low-cost materials incorporated with silver nanoparticles to treat microbial-contaminated drinking water, especially in developing and poor countries.